Multi-scale imaging of high-pressure hydrogen induced damage in EPDM rubber using X-ray microcomputed tomography, helium-ion microscopy and transmission electron microscopy. (15th March 2023) - Kuang, W.; Arey, B.W.; Dohnalkova, A.C.; Kovarik, L.; Mills, B.; Menon, N.C.; Seffens, R.J.; Simmons, K.L.
Abstract: Ethylene propylene diene (EPDM) rubber has gained increasing interest for use in hydrogen infrastructure due to its excellent sealing performance and low temperature properties. However, severe structural damage has been observed in EPDM O-rings after exposure to high-pressure hydrogen. The origination and propagation mechanisms of this damage are poorly understood. To address this knowledge gap, multi-scale imaging leveraging X-ray micro-computed tomography (micro-CT), helium ion microscopy (HeIM), and transmission electron microscopy (TEM) were used in this work to study a series of sulfur-cured ethylene propylene diene (EPDM) rubber materials with varying additives that were exposed to different hydrogen environments. Micro-CT captured the substantial structural damage due to hydrogen exposure; it revealed an association between zinc oxide (ZnO) particles and damage initiation. Further studies by TEM and scanning TEM with energy dispersive X-ray spectroscopy (EDS) were focused on these particles at the micro-to nano-scale range. TEM indicated that hydrogen causes void formation at the interface between ZnO and the rubber matrix. HeIM enabled imaging of surface morphology of the material at high resolution pre- and post-hydrogen exposure while providing information on chemical composition and that cannot be captured by either micro-CT or TEM. Highlights: XCT suggests that cracks are likely to occur around ZnO agglomerates after exposure to high-pressure hydrogen. HeIM reveals that pressure cycling provokes damage growth, whereas fillers counter the damage evolution process. Filled rubber compounds show improved resistance to hydrogen damage compared with unfilled systems. TEM with EDS captures structural alteration around ZnO agglomerates as indicative of initiation of hydrogen damages.